2023
DOI: 10.1007/s00702-023-02609-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and benefits of home initiation of subcutaneous apomorphine infusion for patients with Parkinson’s disease: the APOKADO study

Abstract: Continuous subcutaneous apomorphine infusion (CSAI) is used to treat patients with Parkinson’s disease (PD) who are experiencing motor fluctuations. However, the need to initiate this treatment during a hospital stay may restrict patients’ access to it. To assess the feasibility and benefits of initiating CSAI in the patient’s own home. A French prospective multicenter longitudinal observational study (APOKADO) among patients with PD who required subcutaneous apomorphine, comparing in-hospital versus home init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Our study showed that CSAI has a beneficial effect on both motor and non-motor symptoms of PD and the fact that it can be used as an option in those who are not candidates for surgical therapies, such as deep brain stimulation, extends its range of utilization. The recently published APOKADO study shows that home initiation of CSAI is feasible and improves patients’ QoL more quickly with the same level of tolerance as with in-hospital initiation 51 . This approach is less expensive and may make it easier for patients to access CSAI.…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed that CSAI has a beneficial effect on both motor and non-motor symptoms of PD and the fact that it can be used as an option in those who are not candidates for surgical therapies, such as deep brain stimulation, extends its range of utilization. The recently published APOKADO study shows that home initiation of CSAI is feasible and improves patients’ QoL more quickly with the same level of tolerance as with in-hospital initiation 51 . This approach is less expensive and may make it easier for patients to access CSAI.…”
Section: Discussionmentioning
confidence: 97%
“…Outpatient [13] or inpatient CSAI initiation was provided under the supervision of a neurologist and/or a PC physician (see Tables 1-4). A PD nurse (either from the hospital or home care services) was systematically involved to ensure PD evaluation, optimal use of infusion material, provide skin care, and monitor CSAI-related side effects.…”
Section: Patients Characteristics Are Described In Tablesmentioning
confidence: 99%
“…The setting for treatment initiation is also important, with most patients requiring hospital-initiated apomorphine therapy to ensure precise drug delivery (9,10). Overcrowded hospitals remain a challenge, delaying the commencement of such therapies in new patients (11); hence, home-initiated apomorphine therapy has emerged as a solution in this context. Nevertheless, the increasing demand for PDNSs poses a new issue for introducing this treatment in clinic or at home (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowded hospitals remain a challenge, delaying the commencement of such therapies in new patients (11); hence, home-initiated apomorphine therapy has emerged as a solution in this context. Nevertheless, the increasing demand for PDNSs poses a new issue for introducing this treatment in clinic or at home (10,11). Therefore, it is necessary to establish specialized centers with proper equipment and trained interdisciplinary staff (9,12).…”
Section: Introductionmentioning
confidence: 99%